2017
DOI: 10.24843/eeb.2017.v06.i10.p07
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Firm Size Dan Growth Opportunity Terhadap Cash Holding Dan Firm Value

Abstract: This research aims to determine the effect of firm size and growth opportunity to cash holding and firm value. Manufacturing companies that listed in Indonesian Stock Exchange are used as population. Annual ?nancial data of 38 ?rms from manufacturing companies listed on Indonesian Stock Exchange from 2013 to 2016 examined as sample. Path analysis technique used to analysis hypothesis of  the research by SPSS software. The results showed that: firm size and growth opportunity had positive and significant impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 4 publications
2
4
1
5
Order By: Relevance
“…Thus, the second hypothesis (H2) is not rejected. The results of this study are in line with the results of studies of Luo & Hachiya (2005), Sola et al (2013), Loncan & Caldeira (2014), Thanh (2015) and Liestyasih & Wiagustini (2017), who found that cash holding has a positive effect on firm value. This means that the greater the amount of cash holding a company has, the higher the value of the company.…”
Section: The Effect Of Cash Holding On Company Valuesupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, the second hypothesis (H2) is not rejected. The results of this study are in line with the results of studies of Luo & Hachiya (2005), Sola et al (2013), Loncan & Caldeira (2014), Thanh (2015) and Liestyasih & Wiagustini (2017), who found that cash holding has a positive effect on firm value. This means that the greater the amount of cash holding a company has, the higher the value of the company.…”
Section: The Effect Of Cash Holding On Company Valuesupporting
confidence: 91%
“…Research conducted by Liestyasih & Wiagustini (2017) also shows the same results, cash holding is considered capable of improving company performance by reducing external funding costs and providing added value in meeting investment opportunities. This supports signaling theory where cash holding will give a positive signal to the public about the company's ability to maintain liquidity and increase productivity so that it will increase the value of the company.…”
Section: The Effect Of Cash Holding On Company Valuementioning
confidence: 61%
“…Berdasarkan kasus tersebut dapat dilihat jika kurangnya kontrol terhadap cash holding dapat mengakibatkan perusahaan mengalami kekurangan kas dan tidak dapat melunasi utangnya. Liestyasih (2017) menyatakan bahwa kas memiliki fungsi untuk menjalankan operasi perusahaan sehingga tanpa kas perusahaan akan sulit untuk mempertahankan operasinya dan pengambilan keputusan cash holding menjadi salah satu yang harus diperhatikan Pengaruh Growth Opportunity, Leverage, Firm Size dan Profitabilitas Terhadap Cash Holding | 3 JRA, 2022, 6(1), 1-15 oleh manajer. Terdapat beberapa faktor yang dapat mempengaruhi cash holding yaitu growth opportunity, leverage, firm size dan profitabilitas.…”
Section: Pendahuluanunclassified
“…Teori ini membuat perusahaan tidak mempunyai target kas optimal, sehingga perusahaan akan cenderung menyimpan sisa kas dari hasil kegiatan operasionalnya (Agung, 2019). Liestyasih (2017) menyatakan bahwa pecking order theory menjelaskan tentang pemilihan alternatif sumber pembiayaan perusahaan, dimana dijelaskan dalam teori ini bahwa penggunaan sumber dana internal (laba ditahan dan cash holding) menjadi pilihan utama perusahaan. Kas disebut berperan sebagai penyangga laba ditahan dengan kebutuhan investasi, sehingga saat laba ditahan serta kas tidak lagi dapat mencukupi barulah digunakan pembiayaan eksternal.…”
Section: Tinjauan Pustakaunclassified
“…Pertumbuhan perusahaan dapat dijadikan indikator perkembangan perusahaan yang baik dengan meningkatkan laba perusahaan (Said & Mande, 2020). Peningkatan growth opportunity dapat berfungsi sebagai sinyal yang baik untuk pertumbuhan masa depan perusahaan (Liestyasih & Wiagustini, 2017).…”
Section: Tinjauan Pustakaunclassified